Average Error: 0.0 → 0.0
Time: 16.5s
Precision: 64
\[\sqrt{1 - x} + {x}^{y}\]
\[\sqrt{1 - x} + {x}^{y}\]
\sqrt{1 - x} + {x}^{y}
\sqrt{1 - x} + {x}^{y}
double f(double x, double y) {
        double r756200 = 1.0;
        double r756201 = x;
        double r756202 = r756200 - r756201;
        double r756203 = sqrt(r756202);
        double r756204 = y;
        double r756205 = pow(r756201, r756204);
        double r756206 = r756203 + r756205;
        return r756206;
}

double f(double x, double y) {
        double r756207 = 1.0;
        double r756208 = x;
        double r756209 = r756207 - r756208;
        double r756210 = sqrt(r756209);
        double r756211 = y;
        double r756212 = pow(r756208, r756211);
        double r756213 = r756210 + r756212;
        return r756213;
}

Error

Bits error versus x

Bits error versus y

Try it out

Your Program's Arguments

Results

Enter valid numbers for all inputs

Derivation

  1. Initial program 0.0

    \[\sqrt{1 - x} + {x}^{y}\]
  2. Final simplification0.0

    \[\leadsto \sqrt{1 - x} + {x}^{y}\]

Reproduce

herbie shell --seed 1 
(FPCore (x y)
  :name "sqrt(1-x)+pow(x,y)"
  :precision binary64
  (+ (sqrt (- 1 x)) (pow x y)))